Evaluating the Polyphenol Profile in Three Segregating Grape (Vitis vinifera L.) Populations - Alberto Hernández-Jiménez; Rocío Gil-Muñoz; Yolanda Ruiz-García; Jose María López-Roca; Adrián Martinez-Cutillas; Encarna Gómez-Plaza (Journal of Analytical Methods in Chemistry)
This paper explores the characteristics of the anthocyanin and flavonol composition and content in grapes from plants resulting from intraspecific crosses of Vitis vinifera varieties Monastrell × Cabernet Sauvignon, Monastrell × Syrah, and Monastrell × Barbera, in order to acquire information for future breeding programs. The anthocyanin and flavonol compositions of twenty-seven hybrids bearing red grapes and 15 hybrids bearing white grapes from Monastrell × Syrah, 32 red and 6 white from Monastrell × Cabernet Sauvignon, and 13 red from Monastrell × Barbera have been studied. Among the intraspecific crosses, plants with grapes presenting very high concentrations of anthocyanins and flavonols were found, indicating a transgressive segregation for this character, and this could lead to highly colored wines with an increased benefits for human health. As regards the qualitative composition of anthocyanins and flavonols, the hydroxylation pattern of the hybrids that also may influence wine color hue and stability presented intermediate values to those of the parentals, indicating that values higher than that showed by the best parental in this respect will be difficult to obtain. The results presented here can be helpful to acquire information for future breeding efforts, aimed at improving fruit quality through the effects of flavonoids.